Social Media Dialogues on Immigration Policy: The Case of Operation Dudula - Mmotong, Thabiso (University of the Witwatersrand, Johannesburg, 2024)
In the democratic context of South Africa, where public engagement mechanisms are limited, there exists a risk of citizen disenfranchisement and internal conflicts. This study advocates for participatory governance and harnesses the power of social media to actively involve citizens and stakeholders in shaping immigration policies. Recognizing the transformative potential of online platforms, the goal is twofold: to critique existing inadequacies and contribute to more inclusive and responsive governance models. By bridging the gap between policymakers and the public, this endeavour aims to foster informed and harmonious discourse on immigration policy. The paper specifically examines Operation Dudula, a grassroots movement that has garnered attention for its immigration-focused stance. Through qualitative research methods, the study sheds light on societal perspectives regarding immigration policy in South Africa. The analysis focuses on publicly shared Twitter posts, including those associated with the hashtag #OperationDudula and content from the official Operation Dudula account. This study provides a window into the intricate landscape of South African immigration policy, revealing a dynamic discourse that unfolds across social media platforms. It spotlights the pivotal role of citizen engagement in shaping immigration policy. Participants demonstrate a collective commitment to grappling with the complexities inherent in immigration. The research advocates for proactive measures, emphasizing the need for transparent and inclusive communication practices. By actively engaging with diverse perspectives on social media, we can foster an environment conducive to informed dialogue. Furthermore, the study champions initiatives focused on citizen education and empowerment, aiming to facilitate meaningful participation in the formulation of immigration policies.
A research report submitted in fulfillment of the requirements for the Master of Management, In the Faculty of Faculty of Commerce, Law and Management, Wits School of Governance, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Immigration policy; Social Media; Twitter/X; Operation Dudula; Glo-Cal Politics; Informal Policy Approaches; SDG-9: Industry, innovation and infrastructure